PENGARUH e-WOM TERHADAP DESTINATION IMAGE DAN ATTITUDE TERHADAP TRAVEL INTENTION DI NUSA PENIDA BALI, INDONESIA - Denny A. Wenas; Priscillia M. Tjandra; Aurelia Evelyn Sucipto; Nathanella A. Fo; Brillian P. P. Pusung; Sabar Pria N. Simanjuntak; Juliani Dyah Trisnawati (Universitas Triatma Mulya, 2023)
This study aims to identify theoretical arguments and hypotheses also analyzing interrelationship between influence of e-WOM, destination image, and attitude towards tourists’ travel intention at Nusa Penida, Bali, Indonesia. With a total of 229 online respondents participated in this study. Primary data were obtained from an online survey using Google Form with likert scale. Author evaluated data using SPSS 27.0 to assess the validity and reliability test, also used AMOS 26.0 Graphic to analyze the Structural Equation Model (SEM) and examine the hypothesis result. The results of the analysis confirm that e-WOM is affecting destination image but not significant, also affecting tourists’ attitude and travel intention significantly. However, the destination image had a negative affect towards travel intention significantly and tourists’ attitude affected travel intention significantly. The results of this research will contribute to the fields of tourism destination marketing, e- commerce, tourist destination branding, and e-tourism. This study assists tourism organizations in the development and implementation of destination marketing strategies in Indonesia.